The effects of tumor treating fields and temozolomide in MGMT expressing and non-expressing patient-derived glioblastoma cells. (February 2017) - Clark, Paul A.; Gaal, Jordan T.; Strebe, Joslyn K.; Pasch, Cheri A.; Deming, Dustin A.; Kuo, John S.; Robins, H. Ian
Highlights: Tumor treating fields (TTFs) & temozolomide (TMZ) in TMZ resistant & sensitive cells. All cell lines were equally sensitive to the inhibitory effects of TTFs. Inhibitory effect of TTFs was independent of TMZ and did not overcome TMZ resistance. The optimum frequency for TTFs (200 kHz) was the same frequency used clinically. Abstract: A recent Phase 3 study of newly diagnosed glioblastoma (GBM) demonstrated the addition of tumor treating fields (TTFields) to temozolomide (TMZ) after combined radiation/TMZ significantly increased survival and progression free survival. Preliminary data suggested benefit with both methylated and unmethylated O-6-methylguanine-DNA methyl-transferase (MGMT) promoter status. To date, however, there have been no studies to address the potential interactions of TTFields and TMZ. Thus, the effects of TTFields and TMZ were studied in vitro using patient-derived GBM stem-like cells (GSCs) including MGMT expressing (TMZ resistant: 12.1 and 22 GSC) and non-MGMT expressing (TMZ sensitive: 33 and 114 GSC) lines. Dose-response curves were constructed using cell proliferation and sphere-forming assays. Results demonstrated a ⩾10-fold increase in TMZ resistance of MGMT-expressing (12.1 GSCs: IC50  = 160 μM; 22 GSCs: IC50  = 44 μM) compared to MGMT non-expressing (33 GSCs: IC50  = 1.5 μM; 114 GSCs: IC50  = 5.2 μM) lines. TTFields inhibited 12.1 GSC proliferation at all tested doses (50–500 kHz) with an optimal frequency of 200 kHz. At 200 kHz, TTFields inhibited proliferation and tumor sphere formation of both MGMT GSC subtypes at comparable levels (12.1 GSC: 74 ± 2.9% and 38 ± 3.2%, respectively; 22 GSC: 61 ± 11% and 38 ± 2.6%, respectively; 33 GSC: 56 ± 9.5% and 60 ± 7.1%, respectively; 114 GSC: 79 ± 3.5% and 41 ± 4.3%, respectively). In combination, TTFields (200 kHz) and TMZ showed an additive anti-neoplastic effect with equal efficacy for TTFields in both cell types (i.e., ± MGMT expression) with no effect on TMZ resistance. This is the first demonstration of the effects of TTFields on cancer stem cells. The expansion of such studies may have clinical implications.